2017
DOI: 10.1371/journal.pone.0171494
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry, questionnaire and electronic medical record based COPD in a population survey: Comparing prevalence, level of agreement and associations with potential risk factors

Abstract: BackgroundCOPD-diagnosis is confirmed by post-bronchodilator (BD) spirometry. However, epidemiological studies often rely on pre-BD spirometry, self-reports, or medical records. This population-based study aims to determine COPD-prevalence based on four different operational definitions and their level of agreement, and to compare associations between COPD-definitions and risk factors.MethodsCOPD-prevalence in 1,793 adults from the general Dutch population (aged 18–70 years) was assessed based on self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 31 publications
3
33
0
2
Order By: Relevance
“…The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32]. Moreover, although less research has focused on respiratory patients, the higher rates of respiratory symptoms and infections we found in COPD patients in the exposed areas seem to be in agreement with findings of earlier studies in the Netherlands [17,18].…”
Section: Discussionsupporting
confidence: 87%
“…The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32]. Moreover, although less research has focused on respiratory patients, the higher rates of respiratory symptoms and infections we found in COPD patients in the exposed areas seem to be in agreement with findings of earlier studies in the Netherlands [17,18].…”
Section: Discussionsupporting
confidence: 87%
“…It is relevant to note that at the time of our study, Q-fever incidence had dropped again to pre-epidemic levels (Freidl et al, 2017). Moreover, all study participants underwent serological testing for antibodies against C. burnetii, as part of the health assessment of the VGO study (Borlée et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…We recently assessed the daily mobility (Klous et al, 2017) of a representative subsample (Supp. Table 1, (Borlée et al, 2015;Freidl et al, 2017;Borlée et al, 2017)) of the VGO cohort study to enable exploring differences in exposure to livestock based on the Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…14 The overall COPD prevalence in our presentation is consistent with other studies elsewhere, where LLN was used for COPD diagnosis. 14,19 Despite its better accuracy, LLN approach is limited to the use of predicted values. In Kazakh population, predicted values have never been published, whereas widely used Global Lung Function Initiative (GLI) 2012 reference equations using spline method did not include any population from Central Asia, and, therefore, have never been tested in this population.…”
Section: Discussionmentioning
confidence: 99%